Significance of bees in pollination and yield increase of old plum and apple cultivars - Jaćimović Vučeta; Nedić Nebojša; Radović Marija; Božović Đina (Agroznanje, 2013)
Farmers and beekeepers want bees to pollinate crops more efficiently. In order to be more efficient, bee themselves prepare their colonies, because the pollination of most crops is early in the season when there is no an abundance of workers bees in the beehive. Numerous fruit species have enormous significance for bees and the development of their colonies in early spring (Hazel, Almond, Cornelian-Cherry, Cherry-Plum, etc.) as well as for preparation for the main pasture. Honey bees present over 85% of fruit trees pollinators, while all other pollinators reach 14-15 %. The aim of this work is to show the percentage of pollinated fruits, i.e., percent fruit set of old plum cultivars, with or without bees, and to determine their influence on the marked trees yield of the examined cultivars. This paper presents two year research (2010-2011) on the role of the honey-bee in pollination of some old plum and apple cultivars in Gornje Polimlje region. Before flowering the flowers were counted on the branches isolated with tulle nets and the ones where the bees had free access. The fruits on marked branches have been numbered after flowering and pollination. The percentage of fruit set in CV. Komperuša on non-isolated branches was 84% and on isolated ones 37.87 %. Of the total number of fruit set in CV. Crveni piskavac before harvest remained 23.55 % on non-isolated branches, while on the isolated remained 11.58 %, which show us that yield is bigger per 50 % if the polination is done by bees.